Highly emissive poly(maleic anhydride-alt-vinyl pyrrolidone) with molecular weight-dependent and excitation-dependent fluorescence. Issue 32 (28th July 2017) - Shang, Cong; Wei, Nan; Zhuo, Hongmei; Shao, Yumei; Zhang, Qin; Zhang, Zexian; Wang, Huiliang
Abstract : Nonconventional poly(maleic anhydride- alt -vinyl pyrrolidone) copolymers exhibit distinct AIE characteristics, as well as molecular weight-dependent and excitation-dependent fluorescence. They can emit blue to red colours under different excitation wavelengths. Abstract : Nonconventional luminescent polymers have attracted rapidly growing attention owing to their importance in the fundamental understanding of fluorescence mechanisms and potential practical applications. However, most non-conjugated luminogens exhibit weak blue emission. Incorporating different nonconventional chromophores and adjusting molecular structures of polymers are assumed to enable the formation of more conformations with strong intra- and/or interchain interactions, leading to strong and red-shifted emissions. In this work, we synthesized poly(maleic anhydride- alt -vinyl pyrrolidone) (PMVP) copolymers with different molecular weights through a conventional free radical precipitation copolymerization method. The emissions of PMVPs are significantly red-shifted in comparison to those of the homopolymers poly(maleic anhydride) and poly( N -vinyl-2-pyrrolidone). The PMVPs exhibit aggregation-induced emission (AIE) characteristics, as they are highly emissive in concentrated solutions or in the solid state. The PMVPs also exhibit significant molecular weight-dependent fluorescence (MWDF) and excitation-dependent fluorescence (EDF). The photoluminescence (PL) intensity of their DMSO solutions increases with decreasing molecular weight and their maximal emission wavelength ( λ maxex) is red-shifted. Moreover, they can emit a wide range of colours from blue to red under different excitation wavelengths. Very impressively, poly(itaconic anhydride- co -vinyl pyrrolidone) (PIVP) copolymers with a lower chain rigidity emit very strong red emission at about 600 nm in a wide excitation wavelength range, which is rarely reported for non-conjugated luminogens. This study may shed some light on the preparation of nonconventional luminescent polymers with strong and red-shifted fluorescence emission.